Kekohesifan Dalam Antologi Cerpen Wajah Indoenesiaku Karya Siswa SMA Flores Lembata - Rosa Dalima Bunga (Ekspektasi: Jurnal Pendidikan Ekonomi, 2017)
One of discourse structure is the element of cohesion. Cohesion is the bonds and relationships that exist in the text. According to Halliday and Hassan, cohesion consists of two kinds, namely lexicaland grammatical elements.The grammatical cohesion is a device or a marker which involves the use of language rules elements. The grammatical cohesion devices that are used to connect the idea among sentences is fairly limited, that are pronouns, nominate, noun phrases, and clausa. While the lexical cohesion namely words or free phrases are able to maintain the cohesive relationship with the sentences preceded or followed. There are two kinds of lexical cohesion, namely reiterasi (repetition) and collocation of words that indicateda close relationship of the place (location).The source of datain this researchis the short storiesanthology“Wajah Indonesiaku”written by Senior High School Students in Lembata, Flores . The writer only focussing on two short stories, they areMutiara di Pantai Oa written by Karolina Karmalinda and Awan Hitam Selimut Bangsakuby Donatus Doni Koli. There were two kinds of cohession that are found in both short stories, they are grammatical and lexical cohesion. Grammatical cohesion consists of personal pronouns, additive (addition) and sequential (sequence) conjunction. While the lexical cohesion consist of repetition (reduplication), hyponymy and hypernymy. Lexical repetion (reduplication) consist of a full repetition, repetition with other forms, and repeat with the replacement.